School Management System - BCP Online Enrollment System: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
During the enrollment period, Admission to Bestlink College of the Philippines encountered alot of difficulties since thousands of students went to the admission office for the requirementsneeded to enroll. It was done manually, which consumed a lot of time for the students and theadmission officers. Also, it burdens the admission officers to manually review the applicationsof thousands of students, and it causes delays in updating students' records and the studentsthemselves. Because of this, the project team came up with the idea of creating an Onlineenrollment System that helps the institution, admission, and students as well. The objective ofthis system is to keep track of and secure student records, save money, and have an easierand faster transaction during the enrollment process.As a result, the client gave feedback and found the system very good in terms of itsfunctionality, reliability, usability, efficiency, maintainability, portability, and only goodconcerning its efficiency. It shows that the system provides a high level of quality and requiresminimal rectifications for improvement. Also, it means the system satisfies the client and therequirements are met.The system has finally been developed and implemented into a new approach with the help ofthe agile methodology, meeting with the client, client testing, gathering information, and theideas of the project team. It is an easier process for the school, admission, and studentsduring enrollment. Overall, an online enrollment system for school management systemsimproves efficiency, accessibility, and communication between all stakeholders involved inthe education process.
Keywords: IT & Management